Work-Related Stressors and Employee Well-Being: The Mediating Role of Perceived Stress - Kandel, Sudarshan (Kalika Journal of Multidisciplinary Research, 2025)
Workplace stress is a critical concern globally, impacting both individual wellbeing and organizational performance. Employees face increasing demands such as heavy workloads, time pressure, role ambiguity, and technological changes, which continuously elevate stress levels. Understanding which stressors most affect employee wellbeing and how they operate is essential for designing effective and sustainable interventions. This study investigates the impact of workplace stress on employee wellbeing, identifying key stressors and exploring the mediating role of perceived stress among healthcare workers in Lumbini Province, Nepal. A quantitative research design was employed using structural equation modeling (SEM) to assess relationships among job-related stressors, perceived stress, and employee wellbeing. Data were collected via structured questionnaires from 403 employees across private and government hospitals using a purposive sampling technique. The results indicate that job insecurity, excessive pressure, role conflict, and workload significantly contribute to perceived stress, which in turn negatively influences employee wellbeing. Perceived stress mediates the relationship between these stressors and wellbeing, confirming its central role in the stress-wellbeing nexus. This study provides empirical evidence that perceived stress is a key mediator linking workplace stressors to employee wellbeing, highlighting the urgent need for targeted stress management interventions in Nepalese healthcare settings. The study is limited to the medical sector and relies on self-reported data, which may introduce bias. Therefore, organizations should implement effective interventions such as stress-reduction programs, clear communication, and workload management to enhance employee wellbeing and performance.